Desenvolvimento de hiperinsuflação pulmonar dinâmica após uma sessão de exercício com cicloergômetro de braço em pacientes com dpoc leve - Ivanaga, Ivan Teruaki [UNIFESP] (2013)
Introduction: Chronic obstructive pulmonary disease (COPD) is a systemic disease that causes airflow limitation and muscle impairment. The most common functional activities in daily living involve the shoulder girdle and some of the muscles may have postural and respiratory functions. Consequently, they cause limitations in the activities of daily living due to dyspnea and dynamic pulmonary hyperinflation (DPH) in patients with COPD. However, to our knowledge there is no study that evaluate the DPH in mild COPD patients during upper limbs exercise. Objective: To evaluate the presence and behavior of DPH during incremental upper limb test and during three endurances tests with different loads in patients with mild COPD. Materials and Method: 21 patients mild COPD (FEV1: 91.7 ± 10.3% predicted) and 20 controls, matched to age, sex, weight, height and BMI were evaluated. Were performed incremental test and three endurance tests, randomly, with loads 50%, 65% and 80% of the maximum workload in the incremental arm ergometer test. In all tests we evaluated ventilatory, metabolic and cardiovascular parameters and inspiratory capacity (IC) before and after exercise. Results: COPD patients presented DPH after incremental test with decrease in IC of – 0.171 ± 0.164 L. In the endurance tests with 50% load the patients did not presented DPH (IC: - 0.065 ± 0.257 L). However, the reduction in IC increased in endurance test with loads of 65% and 80% in the COPD group (IC: - 0.152 ± 0.134 L and - 0.139 ± 0.163 L, respectively) and it was statistically different when compared to the control group. The work loads and exercise time showed no difference compared COPD and controls. Conclusions: Patients with mild COPD have DPH after an incremental test of arm cycle ergometer. With increased effort in arm exercise test there is an increase of DPH and from the exercise with 65% load presents difference between the control group and mild COPD, compared in loads of 50%, 65% and 80% of maximum incremental.